Senior Art Show: The Times - Gutierrez, Bianca (My University, 2025)
This thesis discusses the intersection of immigration policy, corporate greed, and the human cost of systemic exploitation through the lens of visual art. Drawing from personal experiences, political critique, and historical context, the work demonstrates how harmful narratives and profit-driven agendas dehumanize migrants, perpetuate cycles of displacement and vulnerability, and how harmful capitalist ideals seep into feminism rendering it performative. By using symbolism and metaphor, the artwork encourages viewers to face uncomfortable truths about the structures that shape society. This project aims to evoke empathy and understanding but also call for action to the injustices that are both: headliners and underrepresented.
Keywords: art; illustration; social justice; activism